1977
DOI: 10.1017/s0022172400055868
|View full text |Cite
|
Sign up to set email alerts
|

Ecological effects of a deodorant and a plain soap upon human skin bacteria

Abstract: SUMMARYThe effects of a commercial trichlorocarbanilide-containing deodorant soap and a commercial plain soap upon the cutaneous flora of individuals were compared. Using a cross-over design, 21 volunteers (10 women and 11 men) washed their forearms at least once a day with one soap for 3 weeks and then switched soaps for another 4 weeks use. By analysis of variance no significant difference in total colony counts was noted among individuals in their use of the two soaps. With the exception of individual varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A number of conditions have been associated with coryneform bacteria, including erythrasma (Sarkany, Taplin & Blank, 1961), trichomycosis axillaris (Crissey, Rebell & Laskas, 1952) and production of axillary odour (Shehadeh & Kligman, 1963b). There have also been a number of studies which showed that procedures associated with a reduction of axillary odour were correlated with a particular decrease in the axillary coryneform population, for example Somerville (1966), Evans et al (1973), Bibel (1977) and McBride, Duncan & Knox (1977).…”
mentioning
confidence: 99%
“…A number of conditions have been associated with coryneform bacteria, including erythrasma (Sarkany, Taplin & Blank, 1961), trichomycosis axillaris (Crissey, Rebell & Laskas, 1952) and production of axillary odour (Shehadeh & Kligman, 1963b). There have also been a number of studies which showed that procedures associated with a reduction of axillary odour were correlated with a particular decrease in the axillary coryneform population, for example Somerville (1966), Evans et al (1973), Bibel (1977) and McBride, Duncan & Knox (1977).…”
mentioning
confidence: 99%
“…Perhaps the most widely used technique is the scrub method of Williamson (18) involving the standardized scrubbing of a delineated area of skin within a glass cup containing a non-ionic detergent sampling fluid. The literature contains many references t o the use of these techniques to evaluate antibacterial agents and products containing them (19,20,21,22,23).…”
Section: Determination Of Effect On Skin Microfloramentioning
confidence: 99%